Integration of berth allocation and storage allocation problems - Sivrikaya, Özgür Emre. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
Berth allocation and storage allocation problems deal with two very important steps in the optimization of the container terminal operations. Berth allocation problem concentrates on the allocation of berth segments to the vessels. The objective is to nd the proper berthing time and position for a vessel while minimizing the penalty cost that incurs if the service of the vessel cannot be completed until its due time. Storage allocation problem allocates storage locations to containers considering the availability of the storage yard. The objective minimizes the total transportation distance of the containers and the number of reshu ing which can be de ned as relocating a container to remove another one from the storage yard. As the berthing position of a vessel and the storage location of a container, which arrives or departs with that vessel, are related with each other, they have to be considered as an integrated problem. However, the integrated problem is an NP-hard problem and heuristic approaches are needed to solve the larger problem instances. This study details the development of an integrated mathematical model for the berth allocation and the storage allocation problems and o ers di erent solution approaches for the larger real-life instances. The performances of the di erent solution methods for individual containers, in terms of the objective values and solution times, are compared. Grouping containers, its advantages and disadvantages on individual containers are also examined in the scope of this thesis.
Keywords: Mooring of ships -- Mathematical models.; Container terminals -- Mathematical models.